Disguised Observation: A Methodological Tool for Uncovering Grounded Realities - Thapa, Kiran; Paudel, Prabhat; Kandel, Sudarshan (Kalika Journal of Multidisciplinary Research, 2024)
This paper examines disguised observation as a qualitative research tool, emphasizing its methodological significance and practical application in uncovering grounded realities across various disciplines such as psychology, sociology, anthropology, and management. By conducting an extensive literature review across various fields such as Psychology, Sociology, Management, Education, Marketing etc. the study traces the historical origins, theoretical bases, and practical uses of disguised observation. Reviewing 35 journal articles published in between the 1920s and 2023, the study identifies and discusses various methodologies and approaches to disguised observation. The reviewing and discussions highlights how disguised observation reveals genuine behavioural patterns, providing valuable insights into organizational dynamics and social interactions. Ethical concerns, especially surrounding informed consent and privacy, are addressed, emphasizing the need for balance between methodological rigor and ethical responsibilities. This paper advocates for the broader use of disguised observation in research, where hidden dynamics often go unobserved with traditional methods. The conclusion calls for broader adoption of disguised observation methods, recognizing both its advantages and challenges in uncovering hidden dynamics within different discipline.